Réponses

2014-05-28T16:32:14+02:00
2x+y = -4
x-y = 1

on les additionne
2x+y+x-y = -4+1
3x = -3
x = -3/3
x = -1     et -1-y = 1 soit -y = 1+1 soit y = -2
  • Utilisateur Brainly
2014-05-28T16:34:38+02:00
2x+y=-4
x-y=1

par substitution :

x = y+1 et je remplace x ds

2x+y=-4

2(y+1)+y = -4
2y+2+y = -4
3y = -2-4
3y = -6
y = -2

x-y = 1
x-(-2) = 1
x+2 = 1
x  =-2+1
x =-1

verif :
2x+y = -4
-2-2 = -4



2x+y=4
2x + y=4
x-y=1
2x=4-y  x= 4-y/2
(4-y/2)-y=1
x=4-y/2
4-y-2y/2=14-3y=1×2-3y=-2 y=3/2
x=4-3/2÷2x=5/3